Building Augmented Reality Integrated Automated Supervisory Flush Valve Testing System - Le, Xuan Thuyen; Tran, Ngoc Huy (Applied mechanics and materials, 2023)
The plastic manufacturing industry, like many other manufacturing industries, is going through great and rapid changes since the 4th industrial revolution. In addition to more conventional innovations such as factory automation, this industry has started to experience more advanced technologies like Internet of Things, augmented reality,... This article presents a case study on the applicability of automation and several technologies from the 4th industrial revolution to the plastic manufacturing industry. To be more specific, the article will demonstrate the process of building a semi-automated flush valve testing system to replace the manual testing process and integrating monitoring, data acquisition, and augmented reality technologies into the above system. The results compared with the manual testing process at a sanitary accessory manufacturing in Vietnam show that the application of those technologies is possible and can solve many issues commonly found in the manual testing process.